The radicalisation of a Swedish ecclesiastical critic of apartheid – Gunnar Helander - Hale, F. (Koers, 2011)
From the 1950s through the 1980s, both the government of Sweden and various non-governmental agencies in that country stood at the forefront of the international campaign against apartheid. To a considerable extent, representatives of the Church of Sweden Mission were involved in this struggle. Among them was Gunnar Helander (1915-2006), a missionary in Natal and on the Witwatersrand from 1938 until 1956. After he returned permanently to Sweden, his role escalated and became known internationally, especially due to his prominence in the leadership of the International Defence and Aid Fund. Between 1949 and 1986 Helander wrote seven novels set in South Africa. In these works one can trace the unfolding of his position on apartheid, which evolved from mild criticism of race relations in South Africa to advocacy of international subversion of the P.W. Botha regime.